Academic Fit and Workplace Reality: An Evaluation of the Informatics Internship Program at UHN I Gusti Bagus Sugriwa Denpasar - Kartika, Luh Gede; Saskara, I Putu Adi; Sanjaya, I Gede Wahyu (International Journal of Social Studies, 2026)
Internships are widely recognized as a key mechanism for bridging academic learning and professional practice, yet their effectiveness depends on multiple contextual and pedagogical factors. This study aims to evaluate the effectiveness of an Informatics internship program by examining (1) the relationship between the academic relevance of internship tasks and students’ theory-to-practice experience, and (2) differences in applied learning outcomes across placement types. A mixed-method approach was employed, combining quantitative analysis of questionnaire data (n = 33) with qualitative feedback from students and partner institutions. Simple linear regression was used to assess the predictive effect of academic relevance, while one-way ANOVA with Tukey HSD post-hoc testing compared outcomes across placement contexts. The results indicate that academic relevance does not significantly predict theory-to-practice experience, suggesting that other factors—such as task diversity, supervision quality, and organizational learning environment—play more substantial roles. However, significant differences were found across placement types (F = 3.25, p = 0.026), with students in private IT companies and village offices reporting higher levels of applied learning compared to those in state-owned enterprises. Qualitative findings further reveal that technically engaging tasks, active supervision, and opportunities for real-world problem solving are critical in enhancing experiential learning, whereas administrative-dominated placements tend to limit skill development. These findings highlight that internship effectiveness extends beyond curriculum alignment and is strongly influenced by the quality and context of workplace learning. This study contributes to the refinement of work-integrated learning models within the Merdeka Belajar–Kampus Merdeka (MBKM) framework and offers practical implications for improving internship design, industry collaboration, and curriculum alignment in Informatics education.